Evaluation of the Co–Go–Me angle as a predictor in Class II patients treated with Herbst appliance and skeletal anchorage: a retrospective cohort study - Manni, Antonio; Migliorati, Marco; Boggio, Andrea; Drago, Sara; Paggi, Elena; Calzolari, Chiara; Gastaldi, Giorgio; Cozzani, Mauro (Frontiers in Oral Health, 2024)
A Co-Go-Me angle threshold of 125.5° was introduced as a cephalometric mandibular response predictive parameter in orthopedic treatment of growing Class II patients with functional appliances, despite some contradictions in literature. Considering the lack of studies that evaluated the role of skeletal anchorage, the aim of this investigation was to reassess the threshold of 125.5° in Co-Go-Me angle as useful predictor in growing skeletal Class II patients treated with acrylic-splint Herbst Appliance and two miniscrews in the lower arch (STM2).Methods: 35 consecutively treated patients (20M, 15 F; mean age 11.37years) with mandibular retrusion were classified into two groups according to their Co-Go-Me baseline value (<125.5° Group 1, and >125.5° Group 2). The STM2 Protocol involved the use of MTH Herbst appliance with acrylic splint in the lower arch and two interradicular miniscrews, as anchorage reinforcement. A cephalometric analysis was performed by the same operator for each patient at baseline (T0) and at the end of Herbst phase (T1). The effects of time and group on the variables were assessed by repeated measures ANOVA. The primary outcome of the research was the difference between groups in mandibular responsiveness to the treatment, intended as relative difference (T1-T0) in Co_Gn.The mean duration of the treatment was 9.5 months. No statistically significant differences between groups were detected at baseline, except from expected SN/GoMe° (p < 0.001) and Co-Go mm(p=0.028). No statistically significant changes between groups, due to the treatment, were found considering mandibular sagittal and vertical skeletal parameters. Similarly, no statistically significant differences were found in dental changes between high-angle and low-angle patients, apart from upper molars sagittal position (p=0.013).Discussion and conclusions: The 125.5° threshold in the Co-Go-Me value was not a reliable predictive parameter for mandibular response in growing patients treated with MTH Herbst and lower skeletal anchorage. The STM2 technique, due to its effective control in sagittal and vertical planes, might be an appropriate protocol in treatment of skeletal class II patients, regardless of the growth pattern.